2021
DOI: 10.1007/s40617-021-00569-5
|View full text |Cite|
|
Sign up to set email alerts
|

A Large-Scale Naturalistic Evaluation of the AIM Curriculum in a Public-School Setting

Abstract: This study evaluated the effectiveness of the AIM curriculum when implemented in a public-school setting by schoolteachers and direct care staff. Three hundred eighteen students took part in this quasiexperimental design where all received the AIM curriculum every day for an entire school year. The participants completed a series of self-assessments (the Avoidance and Fusion Questionnaire for Youth, the Child and Adolescent Mindfulness Measure, and the Strength and Difficulties Questionnaire) at the onset of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Research on the ACT with children has been conducted through both direct observation of behavior (Wilson et al, 2022) and self-report measures (Enoch & Dixon, 2019); effects have been demonstrated through a combination of single case and group design studies (Coyne et al, 2011). In fact, there are even ACT-based curricula explicitly designed and adapted for use with children (e.g., Dixon, 2014; Dixon & Paliliunas, 2017).…”
Section: Behavior Analysis and Actmentioning
confidence: 99%
“…Research on the ACT with children has been conducted through both direct observation of behavior (Wilson et al, 2022) and self-report measures (Enoch & Dixon, 2019); effects have been demonstrated through a combination of single case and group design studies (Coyne et al, 2011). In fact, there are even ACT-based curricula explicitly designed and adapted for use with children (e.g., Dixon, 2014; Dixon & Paliliunas, 2017).…”
Section: Behavior Analysis and Actmentioning
confidence: 99%
“…More recent discussions on the superiority of SSDs have echoed similar sediments (Kyonka et al, 2019). Examples of group design methods and statistical analyses will occasionally appear in behavior analytic journals today (e.g., Dixon et al, 2022;Jang et al, 2012, Sutton et al, 2022Silverman et al, 2007;Yi et al, 2022), yet they are a minority compared to the continued use of SSDs throughout. Even with such examples appearing within our own collection of scholarly journals, most behavior analytic textbooks fail to describe the rationale and usage of group methods and analyses for behavior analysts (Cooper 2007;Mayer et al, 2019;Sidman, 1960; yet see Belisle et al, 2021 as an exception) -thus potentially limiting an awareness of value and an understanding of how to construct research questions utilizing group designs.…”
Section: Introductionmentioning
confidence: 99%